Doppler ultrasound - Kiran Easwaran. (2009)
Ultrasound imaging is widely used in medicine. It is possible to perform both diagnosis and therapeutic procedures with this imaging technique. Medical ultrasonography is used in various applications in medicine including Cardiology, Endocrinology, Gastroenterology, Gynecology,Obstetrics, Ophthalmology, Urology and many more. Diagnostic Ultrasound has since been imported into practically every other area of medicine.